1981
DOI: 10.1161/01.hyp.3.6.730
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I, II, and III in sheep. A model of angiotensin production and metabolism.

Abstract: SUMMARY The arterial and centra] venous concentrations of angiotensin I (AI), Val'-anglotensln II ([Val' 3-8)), both peptides could be found in arterial blood. 1 The calculated blood clearance rates of these two smaller fragments of angiotensin were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…Both angiotensin I and angiotensin II are present in venous blood in concentrations far too high to be explained by their generation in the blood alone, especially given the extensive conversion of angiotensin I to angiotensin II and the clearance of both peptides across peripheral tissues [29]. This has led to the proposal that tissue angiotensin production contributes to angiotensin concentrations in plasma [29,30]. Several studies have suggested that vascular tissue can release angiotensin peptides into plasma by mechanisms independant of renal renin release [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Both angiotensin I and angiotensin II are present in venous blood in concentrations far too high to be explained by their generation in the blood alone, especially given the extensive conversion of angiotensin I to angiotensin II and the clearance of both peptides across peripheral tissues [29]. This has led to the proposal that tissue angiotensin production contributes to angiotensin concentrations in plasma [29,30]. Several studies have suggested that vascular tissue can release angiotensin peptides into plasma by mechanisms independant of renal renin release [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…First, a number of groups have shown the generation of both angiotensin I and II by isolated vascular preparations, notably the hind quarter of the rat [3-6]. Second, a few studies have care fully analysed the metabolism and produc tion of angiotensin I across various vascular beds in vivo and shown that a large turnover in angiotensin I occurs across many vascular beds with local generation replacing that taken up from the circulation [1,7,8]. Thus, considerable data now indicate that local production of both angiotensin I and II oc curs in the vascular wall.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the direct adsorption of renin in plasma and its loss upon bilateral nephrectomy has been dem onstrated [13]. The importance of vascular wall renin has been recognized by comparing the rate of clearance of angiotensins in var ious organs and the rate of production of angiotensins by the plasma renin system by the classical endocrine mechanism [14][15][16], The plasma renin activity was found to be insufficient for maintaining the plasma level of angiotensins which are cleared rapidly during passage through various organs. Thus, the importance of vascular wall renin had to be invoked.…”
Section: Introductionmentioning
confidence: 99%